Perancangan Sistem Informasi Akuntansi Harga Pokok Produksi Berdasarkan Job Order Costing - Sayyidah Nabila Azahra; S Supriyati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2022)
Digital transactions that are increasingly developing make the use of technology in various company businesses increasingly needed. In manufacturing companies there is a calculation of the cost of production (HPP) which is the most important part in calculating the costs incurred during the production process. However, human error problems often arise when HPP calculations are still done manually, one of which is at the Liwet Asep Strawberry company. The purpose of this study was to design an accounting information system for the cost of goods manufactured at Liwet Asep Strawberry, which currently determines the cost of production that is not in accordance with accounting standards. The instability of the cost of production can affect the increase in production costs resulting in the company's profit or loss so that it cannot be monitored by managers, besides that the accounting records have not been computerized so that it can hamper the processing time of the cost of goods manufactured report. The information system designed by the author uses the PHP programming language and the PostgreSQL database. The information system design model used is a context diagram and flowchart and a system development model using the waterfall SDLC model. The purpose of designing this system is to assist in the process of recording, calculating and reporting the cost of production effectively and efficiently. The result of this design is that it can improve the performance of making reports on the cost of production.